Comparative efficacy of anti‐diabetic agents on nonalcoholic fatty liver disease in patients with type 2 diabetes mellitus: a systematic review and meta‐analysis of randomized and non‐randomized studies‡. Issue 2 (1st November 2015) - Tang, Wenjuan; Xu, Qianyue; Hong, Ting; Tong, Guoyu; Feng, Wenhuan; Shen, Shanmei; Bi, Yan; Zhu, Dalong
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) has a high prevalence in patients with type 2 diabetes mellitus (T2DM). In this study, we sought to provide a comprehensive assessment regarding the effects of anti‐diabetic agents on NAFLD in patients with T2DM. Methods: MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials were searched for randomized controlled trials (RCTs) with different anti‐diabetic agents in T2DM. Observational trials were also recruited to expand our population. Hepatic fat content and liver histology were evaluated as primary outcomes. Pooled estimates were calculated using a fixed effect model. Results: One thousand one hundred ninety‐six participants in 19 RCTs and 14 non‐randomized studies were included. Evidence from RCTs and observational studies suggested that greater hepatic fat content reduction and improved liver histology were seen in thiazolidinediones for 12–72 weeks; glucagon‐like peptide‐1 receptor agonists had beneficial effects on hepatic fat content after 26–50 weeks intervention, and insulin/metformin combination with 3–7 months improved hepatic fat content. Initiating metformin or dapagliflozin showed no benefit on hepatic fat content or liver histology in 16–48 weeks. Besides, nateglinide for 18 months was reported in a small sample‐size RCT to improve hepatic fat content and liver histology. Sitagliptin therapy of 1 year also provided benefit on nonalcoholic steatohepatitis score in an observational study. Conclusions: For T2DM with NAFLD, administrating thiazolidinediones and glucagon‐like peptide‐1 receptor agonists seems to provide more identified advances in attenuating hepatic fat content. Further RCTs are warranted to assess the efficacy of various hypoglycemic agents on clinical outcomes associated with NAFLD in T2DM. Copyright © 2015 John Wiley & Sons, Ltd.